Students’ satisfactions towards food quality, price and value at UiTM Terengganu cafeterias / Siti Noraisah Dolah @ Abdullah - Dolah @ Abdullah, Siti Noraisah (2011)
Institutional foodservice can be defined as a provision of catering and foodservice for an institution. Owing to this definition, university foodservice is perceived to provide related products of food and services to university students. It must not be forgotten that food is vital for human beings including students. Food is an important substance to prolong life, supply energy and endorse growth. With that, providing good quality food to university students is very important. Moreover, good quality food provides good health and thinking and at the same time, the price and value of food provide satisfaction and valuable feeling for their money. With that, the present study examines students’ satisfaction towards food quality, price and value at UiTM Terengganu cafeterias. The researcher conducted the study at three UiTM cafeteria’s namely Perhentian, Redang and Tenggol cafeteria and the data was gathered through self-administered questionnaires. Result showed that, although contented with the importance of food quality attributes, the majority of the students have expressed that the food quality, price and value do not meet their expectations. The results of students’ satisfaction and their intention to patronize these cafeterias are only because there are no other alternatives available for them to dine within the university area. The findings of this study do not only involve students and cafeteria operators but also UiTMT as a whole especially the hostels’ administration.